Efecto de los ejercicios isométricos en adultos mayores con lumbalgia - Añazco Domínguez, Andrés Dayron (2023)
ABSTRACT: The work was carried out to demonstrate the effects of isometric exercises by compiling and reviewing updated bibliographic material for the physiotherapeutic approach in older adults with low back pain by analyzing bibliographic sources of scientific rigor. Thirty-five articles obtained from different scientific databases were used in such a way that the studies collected correspond to clinical, experimental, transversal, prospective randomized and controlled, double-masked controlled, prospective observational, prospective observational, analytical observational, randomized and controlled case studies, which reflect the participation of patients in a physical rehabilitation program through structured training to verify the effects of isometric exercises in older adults with low back pain. The evaluation of the articles to corroborate their methodological quality was carried out through the PEDro scale, for which an evaluation equal to or greater than six was obtained for their validity in scientific research. Low back pain is a common problem in older adults. As they age, the muscles and bones can weaken and lose flexibility, which increases the risk of injury and back pain, limiting their ability to perform daily activities and reducing their quality of life. Isometric exercises are a form of strength training that can help reduce low back pain and improve physical function in this population group. Unlike other exercises, isometric exercises involve contracting muscles without movement and holding a fixed position for a set amount of time. It may benefit older adults with low back pain, improving lumbar stability and reducing the risk of spinal injury. Some of the effects of isometric exercises in older adults with low back pain will be explored, including pain reduction, improved physical function, and lumbar stability. The importance of professional supervision to adapt these exercises to each person's individual needs will also be highlighted.